Vivre avec des animaux « à problème » - Coralie Mounet (Revue de Géographie Alpine)
The presence and recent spread of the wolf and the boar in the mountains of the French Alps are upsetting the organisation of territorial “vivre ensemble” (cohabitation) projects. This article examines how this new situation is being dealt with at the local level and attempts to redefine local life between men and animals. The macro-social approach often adopted in analysing conflicts surrounding “problem” animals is considered to be insufficient and the article attempts to complement this by proposing a micro-geographical perspective that seeks to determine the logic underpinning actors’ behaviour, which until now has been inaccessible. It thus focuses on the role of variability in local situations.